JURIDICAL ANALYSIS OF EVIDENCE IN THE CRIMINAL ACT OF AGGRAVATED ASSAULT (CASE STUDY OF DECISION NUMBER 208/PID.B/2025/PN BNJ) - Wahyudi; Halimatul Maryani (CV. Barokah Publsiher, 2026)
assault according to the provisions of the applicable criminal law consists of the Court summoning witnesses and victims to provide testimony at the trial, the Court conducting physical evidence testing, examination and response of the defendant to defend himself and respond to the evidence presented, the Court assessing witness testimony, physical evidence, and other documents to ensure the truth of the facts. The analysis of evidence for the crime of serious assault in the Decision of the Binjai District Court Number 208 / Pid.B / 2025 / PN Bnj has been carried out correctly by the panel of judges. Criminal liability for the perpetrator of serious assault in the Decision of the Binjai District Court Number 208 / Pid.B / 2025 / PN Bnj is liability with a prison sentence of 5 years because it has been legally and convincingly proven to have committed acts of serious assault against the victim. The defendant's actions were carried out consciously, not under duress or without justification.